MEMBINGKAI KEMBALI ILMU: KAJIAN KRITIS TENTANG DIKHOTOMI ILMU - Duski Samad (AT-TA'LIM, 2012)
The existence of religious science and general science has been the long discourse that reduced the scientific world.  The separation of these two sciences, often refers to as science dichotomy, has brought about serious implication not only to institutions and facilities, but also the main resources of these two branches. More serious implication of the separation of these two sciences has also created the gaps particularly on the superiority of the general science.  This unhealthy and lack of objective view to religious science may not be taken for granted; comprehensive explanations of scientific resources, scientific method, and the historical existence of the two branches should be explored to reshape it in a strong unity and complementary.